Endoscopic and Histological Assessment, Correlation, and Relapse in Clinically Quiescent Ulcerative Colitis (MARQUEE). Issue 2 (14th March 2020) - Osterman, Mark T; Scott, Frank I; Fogt, Franz F; Gilroy, Erin D; Parrott, Susan; Galanko, Joseph; Cross, Raymond; Moss, Alan; Herfarth, Hans H; Higgins, Peter D R
Abstract: Objective: It is difficult to predict relapse in quiescent ulcerative colitis (UC), but newer endoscopic and histological indices could improve this. This study aimed to determine in UC patients in clinical remission (1) the prevalence of active endoscopic and histological disease; (2) the correlation between endoscopic and histological scores; and (3) the predictive power of these scores for clinical relapse. Design: This multicenter prospective cohort study conducted by the Crohn's and Colitis Foundation Clinical Research Alliance included 100 adults with UC in clinical remission undergoing surveillance colonoscopy for dysplasia. Endoscopic activity was assessed using the Mayo endoscopic score (MES), ulcerative colitis endoscopic index of severity (UCEIS), and ulcerative colitis colonoscopic index of severity (UCCIS). Histology was assessed with the Riley index subcomponents, total Riley score, and basal plasmacytosis. Results: Only 5% of patients had an MES of 0, whereas 38% had a score of 2 to 3; using the UCEIS, the majority of patients had at least mild activity, and 15% had more severe activity. Many patients also had evidence of histological disease activity. The correlations among endoscopic indices, histological subcomponents, and total score were low; the highest correlations occurred with the subcomponent architectural irregularity (ρ = 0.43–0.44), total Riley score (ρ = 0.35–0.37), and basal plasmacytosis (ρ = 0.35–0.36). Nineteen patients relapsed clinically over 1 year, with the subcomponent architectural irregularity being the most predictive factor ( P = 0.0076). Conclusions: This multicenter prospective study found a high prevalence of both endoscopic and histological disease activity in clinically quiescent UC. The correlations between endoscopy and histology were low, and the power to predict clinical relapse was moderate.